MAKNA KALIMAT PERINTAH DALAM KITAB “ASBAB WURUD AL-HADIS” (KAJIAN SEMANTIK) - Indah Fadilah; Mohammad Badrus Sholih (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
This article aims to describe the characteristics and meanings of the imperative sentences in the book"Asbab Wurud Al-hadis". Sources of written data in the form of words were used in this study. readingand note-taking techniques used in data collection and research methods used are qualitative researchmethods. The results of this article show that there are various forms of the Prophet's commandments,such as the commands of 6 fi'il-amr, 1 form of ismu fi’il-amr, and 6 lam-amr. And the meaning of thecommand sentence in "Asbab Wurud Al-hadith" includes direct orders, soft orders, and request orders.